The Impact of Renewable Energy Learning Media Based on Local Wisdom on Critical Thinking Skills - Fitrianawati, Meita; Noerazizah, Anggun Septy (International Journal of Learning Reformation in Elementary Education, 2025)
This study aims to assess the effectiveness of renewable energy learning media based on local wisdom in enhancing students' critical thinking skills. A quantitative research approach was employed using a quasi-experimental design, specifically the Nonequivalent Control Group Design. The study involved 27 fifth-grade students from Karangjengkol 03 Elementary School, Cilacap, Indonesia. Data collection instruments included test questions, observation sheets, and documentation. Data analysis was conducted using descriptive and inferential statistics, with hypothesis testing performed through an independent sample t-test. The results indicate a significant improvement in students' critical thinking skills across four assessed aspects following the implementation of the learning media. The t-test results confirm this improvement, with a significance value (Sig. 2-tailed) of 0.000, which is less than the 0.05 threshold. This statistical outcome leads to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (Hₐ), demonstrating that the renewable energy learning media had a measurable effect on students' critical thinking development. Furthermore, the mean post-test score in the experimental class was 84.03, significantly higher than the 48.75 achieved by the control class. This considerable difference in mean scores underscores the effectiveness of the intervention. The higher performance in the experimental group suggests that integrating local wisdom into renewable energy education provides contextualized learning experiences that better engage students and stimulate critical thinking processes compared to conventional teaching methods. These findings provide strong empirical support for the implementation of innovative, culturally relevant instructional strategies in elementary education.